Analysing internet policy as a field of struggle - Julia Pohle; Maximilian Hösl; Ronja Kniep (Internet Policy Review, 2016)
This essay proposes an analytical approach that conceptualises internet policy as a field of struggle which emerges through processes of discursive institutionalisation. By combining field theory and selected Science and Technology Studies (STS) concepts, the essay highlights the performative function of discourses in the field. It does so by showing how actors entered the policy field through the creation of expertise and regulatory competences and uncovers key conflicts that have shaped internet policy. Drawing on interviews and document analysis, the essay illustrates the proposed research approach via three selected examples which demonstrate how international discourses materialised in internet-related organisational structures and regulatory competences in German ministries.